2016
DOI: 10.1186/s12913-016-1641-x
|View full text |Cite
|
Sign up to set email alerts
|

Inspiring health worker motivation with supportive supervision: a survey of lady health supervisor motivating factors in rural Pakistan

Abstract: BackgroundCommunity health worker motivation is an important consideration for improving performance and addressing maternal, newborn, and child health in low and middle-income countries. Therefore, identifying health system interventions that address motivating factors in resource-strained settings is essential. This study is part of a larger implementation research project called Nigraan, which is intervening on supportive supervision in the Lady Health Worker Programme to improve community case management o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 24 publications
2
56
0
Order By: Relevance
“…Jaskiewicz & Tulenko, 2012; Rabbani, Shipton, et al, 2016). Secondly, we found that coronavirus responsiveness has an indirect effect on maternal and neonatal health services via the mediation of employee satisfaction.…”
Section: Discussionsupporting
confidence: 49%
“…Jaskiewicz & Tulenko, 2012; Rabbani, Shipton, et al, 2016). Secondly, we found that coronavirus responsiveness has an indirect effect on maternal and neonatal health services via the mediation of employee satisfaction.…”
Section: Discussionsupporting
confidence: 49%
“…Studies have identi ed the impact of poor structural support; links between insu cient compensation and negative outcomes, including psychological distress [38] or nancial compensation as a key motivator for CHW performance [39,40]. However, monetary recognition is not consistently seen as a singular motivator for work.…”
Section: Discussionmentioning
confidence: 99%
“…However, monetary recognition is not consistently seen as a singular motivator for work. Supportive supervision has shown to address challenges of recognition and improve work output [1,5,40,41] and regular training is positively associated with CHW con dence in their role [1,42]. In order to enhance institutional recognition of the programme, and make further positive health contributions at community level, increased structural support is needed, designed in consultation with RHMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each LHV usually supervises 20-25 LHWs. A supervisor LHV is responsible for training LHWs, and ensuring quality performance by LHWs by collecting monthly reports from the LHWs which provide information on type of cases encountered and relevant services provided (Rabbani et al, 2014(Rabbani et al, , 2016.…”
Section: Lady Health Workers: Primary Carers For Rural Mothers In Pakmentioning
confidence: 99%